A New Lung Ultrasound Protocol Able to Predict Worsening in Patients Affected by Severe Acute Respiratory Syndrome Coronavirus 2 Pneumonia. (6th November 2020) - Perrone, Tiziano; Soldati, Gino; Padovini, Lucia; Fiengo, Anna; Lettieri, Gianluca; Sabatini, Umberto; Gori, Giulia; Lepore, Federica; Garolfi, Matteo; Palumbo, Ilaria; Inchingolo, Riccardo; Smargiassi, Andrea; et al.
Abstract : Objectives: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection can generate severe pneumonia associated with high mortality. A bedside lung ultrasound (LUS) examination has been shown to have a potential role in this setting. The purpose of this study was to evaluate the potential prognostic value of a new LUS protocol (evaluation of 14 anatomic landmarks, with graded scores of 0–3) in patients with SARS‐CoV‐2 pneumonia and the association of LUS patterns with clinical or laboratory findings. Methods: A cohort of 52 consecutive patients with laboratory‐confirmed SARS‐CoV‐2 underwent LUS examinations on admission in an internal medicine ward and before their discharge. A total LUS score as the sum of the scores at each explored area was computed. We investigated the association between the LUS score and clinical worsening, defined as a combination of high‐flow oxygen support, intensive care unit admission, or 30‐day mortality as the primary end point. Results: Twenty (39%) patients showed a worse outcome during the observation period; the mean LUS scores ± SDs were 20.4 ± 8.5 and 29.2 ± 7.3 in patients without and with worsening, respectively ( P < .001). In a multivariable analysis, adjusted for comorbidities (>2), age (>65 years), sex (male), and body mass index (≥25 kg/m 2 ), the association between the LUS score and worsening (odds ratio, 1.17; 95% confidence interval, 1.05 to 1.29; P = .003) was confirmed, with good discrimination of the model (area under the receiver operating characteristic curve, 0.82). A median LUS score higher than 24 was associated with an almost 6‐fold increase in the odds of worsening (odds ratio, 5.67; 95% confidence interval, 1.29 to 24.8; P = .021). Conclusions: Lung ultrasound can represent an effective tool for monitoring and stratifying the prognosis of patients with SARS‐CoV‐2 pulmonary involvement.